Community NetLink - Community Health and Social Services Network (CHSSN) (2006)
Number of pages: 8

Community NetLink - Community Health and Social Services Network (CHSSN) (2006)
Number of pages: 8

Meeting with Simon Brault and Canada Council for the Arts Staff - English Language Arts Network (ELAN) (2006)
Keywords: Official Language Minority Community (OLMC)

Self-Employment and Employment in Quebec's English-speaking Cultural Communities and Visible Minorities : Prospects and Problems - Jedwab, Jack (Youth Employment Services (YES), 2006)
What are the principal barriers to self-employment and employment for members of Quebec’s English-speaking visible minorities and cultural communities? The question is considered in this report in view of the ongoing challenges that some members of English-speaking visible minorities and cultural communities face in the current economy. The specific aim is to improve our understanding of factors which prevent members of Quebec’s English-speaking visible minorities and cultural communities from achieving self-employment and employment goals.

Language Training Program : Findings and recommendations of the lexicon evaluation committee - McLaughlin, Sky; Rogers, Jim (Lexicon Evaluation Committee, 2006)

Rapport de Données de Base 2005-2006 : Accés aux services de santé et aux services sociaux en anglais au Québec - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2006)
Keywords: Official Language Minority Community (OLMC)

Social Support Networks in Quebec's English-speaking Communities : Building Community Vitality Through Social Capital Strategies - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2006)
This report arises in response to one of the objectives of the “We Can Act” project sponsored by the Community Health and Social Services Network (CHSSN). The CHSSN is a network of 60 community resources, associations, foundations, public institutions and other stakeholders dedicated to the development of partnerships in health and social services for English‐speaking communities in Quebec. The CHSSN promotes knowledge‐based community development as a means for communities to enhance their vitality and improve the health and well‐being of their members. Consistent with the population health approach, CHSSN sponsors projects and partnerships which address health determinants affecting the health status of communities as well as supportive strategies to attain a sustainable health and social service system.
Keywords: Official Language Minority Community (OLMC)

The Baseline Data Report 2005-2006 : English-language Health and Social Services Access in Québec - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2006)
Keywords: Official Language Minority Community (OLMC)